Evaluation of Human Mesenchymal Stromal Cells as Carriers for the Delivery of Oncolytic HAdV-5 to Head and Neck Squamous Cell Carcinomas - Robin Nilson; Lea Krutzke; Frederik Wienen; Markus Rojewski; Philip Helge Zeplin; Wolfgang Funk; Hubert Schrezenmeier; Stefan Kochanek; Astrid Kritzinger (Viruses, 2023)
Human multipotent mesenchymal stromal cells (hMSCs) are of significant therapeutic interest due to their ability to deliver oncolytic adenoviruses to tumors. This approach is also investigated for targeting head and neck squamous cell carcinomas (HNSCCs). HAdV-5-HexPos3, a recently reported capsid-modified vector based on human adenovirus type 5 (HAdV-5), showed strongly improved infection of both hMSCs and the HNSCC cell line UM-SCC-11B. Given that, we generated life cycle-unmodified and -modified replication-competent HAdV-5-HexPos3 vector variants and analyzed their replication within bone marrow- and adipose tissue-derived hMSCs. Efficient replication was detected for both life cycle-unmodified and -modified vectors. Moreover, we analyzed the migration of vector-carrying hMSCs toward different HNSCCs. Although migration of hMSCs to HNSCC cell lines was confirmed in vitro, no homing of hMSCs to HNSCC xenografts was observed in vivo in mice and in ovo in a chorioallantoic membrane model. Taken together, our data suggest that HAdV-5-HexPos3 is a potent candidate for hMSC-based oncolytic therapy of HNSCCs. However, it also emphasizes the importance of generating optimized in vivo models for the evaluation of hMSC as carrier cells.